2018
DOI: 10.1002/anie.201805519
|View full text |Cite
|
Sign up to set email alerts
|

A CuO Nanowire‐Based Alternating Current Oxide Powder Electroluminescent Device with High Stability

Abstract: An AC-driven powder electroluminescent (EL) device has been achieved by constructing a CuO nanowire-Zn GeO :Mn phosphor heterogeneous junction. The CuO nanowires enhance the local electric field, resulting in electroluminescence of an oxide-based phosphor in EL devices owing to field injection at the nanowire tips. The CuO nanowire array was synthesized by an in situ thermal oxidation method at 400 °C in air and employed as an electric field enhancement layer in the EL device. The heterogeneous structures were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 51 publications
0
14
1
Order By: Relevance
“…8−10 In particular, electrochemical anodization of various metal substrates can be efficiently used for fabricating one-dimensional nanomaterials such as nanorods and nanoneedles in a suitable electrolyte of appropriate pH. 11−15 Nanomaterials of copper hydroxide and copper oxide have been shown to be efficient in electrochemical energy conversion, 16,17 dye-sensitized solar cells, 18,19 optical applications, 20 electroluminescence, 21 photocatalytic H 2 production, 22,23 and sensing devices. 24,25 Specifically, onedimensional CuO nanomaterials have been used as anodes in lithium and lithium-ion batteries, 26,27 whereas Cu(OH) 2 is preferentially used as a redox-active anode for sensors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…8−10 In particular, electrochemical anodization of various metal substrates can be efficiently used for fabricating one-dimensional nanomaterials such as nanorods and nanoneedles in a suitable electrolyte of appropriate pH. 11−15 Nanomaterials of copper hydroxide and copper oxide have been shown to be efficient in electrochemical energy conversion, 16,17 dye-sensitized solar cells, 18,19 optical applications, 20 electroluminescence, 21 photocatalytic H 2 production, 22,23 and sensing devices. 24,25 Specifically, onedimensional CuO nanomaterials have been used as anodes in lithium and lithium-ion batteries, 26,27 whereas Cu(OH) 2 is preferentially used as a redox-active anode for sensors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As one of the most popular classes of inorganic oxide EL phosphor, Mn 2+ ‐activated zinc germanate (Zn 2 GeO 4 :Mn) phosphor materials have been reported for display applications after bright green EL was achieved in this and related materials . Recently, Zn 2 GeO 4 :Mn phosphor powders have demonstrated EL in our group in conjunction with electrically conductive SiC nanowhiskers and CuO nanowires, indicating the potential to replace ZnS‐based phosphor materials with oxide phosphors to address the low stability issue of AC powder EL devices. These nanoscale architectures provide localized electric field enhancement to achieve EL emission.…”
mentioning
confidence: 96%
“…However, oxide phosphors have long been considered unsuitable for practical applications in high‐field AC powder EL devices; therefore, there has been less interest in AC oxide powder EL devices due to their relatively high operating voltage, although several research groups reported that oxide phosphors could be applied for AC TFEL devices. Recent work has demonstrated the existence of oxide phosphor AC powder EL devices having reduced operating voltage due to the field enhancement effect of conductive nanowires …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Controllable and precise aligning 1D nanomaterials including nanowires (NWs), nanorods, nanofibers, and nanotubes to construct multiscale ordered micropatterns on substrates are essential and significant for various applications such as optoelectronic devices, stretchable electronics, surface enhanced Raman scattering, flexible transparent electrodes, piezoelectric devices, sensing, and artificial electronic skin . Recently, increasing research efforts have been focused on aligning NWs into micropatterns in order to achieve their advantages of integrated physicochemical properties and adequate device performance . In this regard, various solution‐coating techniques have been vigorously developed for their advantages in mild experimental conditions and large‐scale production.…”
mentioning
confidence: 99%